Implementasi Kurikulum Merdeka di Sekolah Dasar Penggerak : (Studi Kasus SD Muhammadiyah 23 Semanggi) - Viona Rosalina, Maritsya Dyah; Amalia , Nur (Jayapangus Press, 2024)
The Merdeka Curriculum which currently implemented in Indonesia is designed to optimize students' knowledge, morals, and characteristics through intracurricular activities, by focusing on competency development. This study aims to find out (1) the history of the establishment of the merdeka curriculum, (2) the implementation of the merdeka curriculum, and (3) its impact on SD Muhammadiyah 23 Semanggi. The research was conducted through qualitative descriptive method. Research data were collected through interviews, observations, and documentation during the period from October to completion. The results of the study showed that SD Muhammadiyah 23 Semanggi was selected as a School of Mover after going through a strict selection process. This program focuses on developing student learning outcomes holistically, creating a pancasila student profile, and strengthening human resources through training and mentoring. The implementation of the Merdeka Curriculum in this school includes diagnostic assessments to understand student needs, make lesson plan, and the use of flexible and creative teaching methods. Learning is carried out through intracurricular activities, co-curricular activities, and projects to strengthen the Pancasila Student Profile. As a result, the Merdeka Curriculum has created a more active and participatory learning environment at SD Muhammadiyah 23 Semanggi. Students develop 21st-century skills, such as critical thinking, creativity, and digital literacy. In addition, teachers and principals play a key role in supporting the success of this implementation. The conclusion of this study shows that the Merdeka Curriculum makes a significant contribution to improving student learning outcomes overall, emphasizing the importance of the role of educators in supporting this change.